Early Enteral Nutrition Tolerance in Patients With Cardiogenic Shock Requiring Mechanical Circulatory Support - Liu, Wen-jun; Zhong, Jun; Luo, Jing-chao; Zheng, Ji-li; Ma, Jie-fei; Ju, Min-jie; Su, Ying; Liu, Kai; Tu, Guo-wei; Luo, Zhe (Frontiers in Medicine, 2021)
Background: Enteral nutrition (EN) is recommended within the first 24– 48 hours for patients with hemodynamic stability, following admission to an intensive care unit (ICU). However, for patients with approximate stable hemodynamics requiring mechanical circulatory support and vasoactive drugs, the application of early EN remains controversial. We sought to evaluate the tolerance of early EN in patients with cardiogenic shock who required vasoactive drugs and mechanical circulatory support after cardiac surgery. Methods: This single-center, prospective observational study included patients with cardiogenic shock, requiring vasoactive drugs and mechanical circulatory support after cardiac surgery, undergoing EN. The primary endpoint was EN tolerance and secondary endpoints were mortality, length of mechanical ventilation, and length of ICU stay. Results: From February 2019 to December 2020, 59 patients were enrolled, of which 25 (42.37%) developed intolerance within 3 days of starting EN. Patients in the EN intolerant group had a longer median length of mechanical ventilation (380 hours vs. 128 hours, p = 0.006), a longer median ICU stay (20 days vs. 11.5 days, p = 0.03), and a higher proportion of bloodstream infections (44% vs. 14.71%, p = 0.018). The median EN calorie levels for all patients in the first 3 days of EN were 4.00 kcal/kg/day, 4.13 kcal/kg/day, and 4.28 kcal/kg/day, respectively. Median protein intake levels of EN in the first 3 days were 0.18 g/kg/day, 0.17 g/kg/day, and 0.17 g/kg/day, respectively. No significant difference was observed in the median dose of vasoactive drugs between groups (0.035 μg/kg/min vs. 0.05 μg/kg/min, p=0.306). Conclusions: Patients with cardiogenic shock after cardiac surgery had a high proportion of early EN intolerance, and patients with EN intolerance had a worse prognosis, but no significant correlation was identified between EN tolerance and the dose of vasoactive drugs.